1986
DOI: 10.1007/bf01800038
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylaspartic aciduria due to aspartoacylase deficiency — a new aetiology of childhood leukodystrophy

Abstract: We describe a male infant with psychomotor retardation and leukodystrophy who excretes large quantities of N-acetylaspartate in his urine. A high CSF/plasma concentration ratio of N-acetylaspartate indicates that this substance originates in the brain. Fibroblasts from the patient are deficient in aspartoacylase activity. It is proposed that the dysmyelination in the patient may be due to failure of N-acetylaspartate to serve as a carrier of acetyl groups from mitochondria to the cytosol for lipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 18 publications
1
71
0
Order By: Relevance
“…Developmental increases in ASPA and NAA correlate with myelination (Burri et al 1991,D'Adamo et al 1973,Kirmani et al 2003 and several studies have shown incorporation of acetate from NAA into myelin lipids (Benuck & D'Adamo 1968,Burri et al 1991,Chakraborty et al 2001,D'Adamo & Yatsu 1966,Mehta & Namboodiri 1995. Total acetate levels and complete myelin lipid synthesis have recently been shown to be deficient in brains of CD knockout mice (Madhavarao et al 2005), providing strong support for the hypothesis that NAA in the CNS supplies acetyl groups for lipid synthesis during myelination (Hagenfeldt et al 1987,Kirmani et al 2002,Kirmani et al 2003,Madhavarao et al 2005,Mehta & Namboodiri 1995. Furthermore, ASPA is found in cells within both cytoplasm and nucleus (Hershfield et al 2006), though its role in the nucleus is yet to be delineated.…”
Section: Introductionmentioning
confidence: 90%
“…Developmental increases in ASPA and NAA correlate with myelination (Burri et al 1991,D'Adamo et al 1973,Kirmani et al 2003 and several studies have shown incorporation of acetate from NAA into myelin lipids (Benuck & D'Adamo 1968,Burri et al 1991,Chakraborty et al 2001,D'Adamo & Yatsu 1966,Mehta & Namboodiri 1995. Total acetate levels and complete myelin lipid synthesis have recently been shown to be deficient in brains of CD knockout mice (Madhavarao et al 2005), providing strong support for the hypothesis that NAA in the CNS supplies acetyl groups for lipid synthesis during myelination (Hagenfeldt et al 1987,Kirmani et al 2002,Kirmani et al 2003,Madhavarao et al 2005,Mehta & Namboodiri 1995. Furthermore, ASPA is found in cells within both cytoplasm and nucleus (Hershfield et al 2006), though its role in the nucleus is yet to be delineated.…”
Section: Introductionmentioning
confidence: 90%
“…Extracellular NAA has been shown to be preferentially taken up by astrocytes as opposed to neurons (Sager et al, 1999b) via the dicarboxylate transporter NaDC3, (Fujita et al, 2005;Ganapathy and Fujita, 2006;George et al, 2004;Huang et al, 2000), and NAA appears in urine at low micromolar concentrations, indicating that there is continuous efflux from the brain (Kelley and Stamas, 1992;Kvittingen et al, 1986;Miyake et al, 1982). Normal serum NAA levels are very low, and this may be due to glomerular filtration in the kidneys (Hagenfeldt et al, 1987). With regard to NAA clearance, it has been estimated that the human brain contains approximately 7 to 8 millimoles of NAA, and that normally about 1% is excreted in the urine per day (Miyake et al, 1982).…”
Section: Naa Transporters and Clearancementioning
confidence: 99%
“…However, other results have failed to show significant ASPA activity in O2A cells in culture (Madhavarao et al, 2002), and immunohistochemical studies have shown a complete lack of ASPA expression in astrocytes in the brain . Considering the facts that astrocytes form a significant portion of the blood-brain barrier, and that NAA is normally found in the urine (Hagenfeldt et al, 1987;Kvittingen et al, 1986), and that astrocytes express a sodium-dependent transporter for the uptake of extracellular NAA (Fujita et al, 2005), it seems likely that these glial cells take up extracellular NAA and excrete it to the circulation. In this regard it is interesting to note that we have observed NAAimmunoreactivity in a sub-population of brain endothelia ( Figure 5).…”
Section: Naa Transporters and Clearancementioning
confidence: 99%
See 2 more Smart Citations